KAMPUS MENGAJAR ANGKATAN 4: MENUJU INDONESIA CERDAS MELALUI KEGIATAN LITERASI, NUMERASI, ADAPTASI TEKNOLOGI DAN ADMINISTRASI DI SD NEGERI 105357 CEMARA, LUBUK PAKAM - Saragih, Rintan; Lumbantoruan, Indriani; Ambarita, Dastin Bastian; Putri, Dea Nirwanda; Turnip, Novia Magdalena; Silalahi, Putri Isabella (Universitas Methodist Indonesia, 2023)
Kampus Mengajar is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs launched by the Ministry of Education, Culture, Research and Technology and supported by the Education Fund Management Institution (LPDP) of the Ministry of Finance. This programe is part of the teaching at schools specially to help students in ellmentary school to assist learning during a pandemic in the 3 areas, whisc is Disadvantaged, Frontier, Outermost by presenting college students as part of strengthening literacy and numeracy. They become a teacher partner in carrying out creativity and innovation in learning. This activity started on 02 August 2022 to 05 December 2022 with the target school SD Negeri 105357 Cemara, Lubuk Pakam, Deli Serdang Regency. Based on the results of the initial mapping, information was obtained that some students could not read and count properly and correctly and had low interest in reading. In addition, the development of soft skills is also needed in the school. Through this activity it is hoped that the school, especially students, can be assisted in terms of increasing numeracy literacy, technology adaptation and administration.